2014
DOI: 10.1371/journal.pone.0107048
|View full text |Cite
|
Sign up to set email alerts
|

Elk3 Deficiency Causes Transient Impairment in Post-Natal Retinal Vascular Development and Formation of Tortuous Arteries in Adult Murine Retinae

Abstract: Serum Response Factor (SRF) fulfills essential roles in post-natal retinal angiogenesis and adult neovascularization. These functions have been attributed to the recruitment by SRF of the cofactors Myocardin-Related Transcription Factors MRTF-A and -B, but not the Ternary Complex Factors (TCFs) Elk1 and Elk4. The role of the third TCF, Elk3, remained unknown. We generated a new Elk3 knockout mouse line and showed that Elk3 had specific, non-redundant functions in the retinal vasculature. In Elk3(−/−) mice, pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 45 publications
1
11
0
Order By: Relevance
“…The challenge in understanding the phenotypes after Mef2 ablation comes because individual loss of different genes required during sprouting angiogenesis can result in vastly different consequences. While depletion of Dll4 levels can have a proangiogenic effect, loss or depletion of direct MEF2 targets ETS1, ELK3, and HLX can have anti-angiogenic effects in vivo (Pham et al 2007;Wei et al 2009;Herbert et al 2012;Weinl et al 2014). Furthermore, the vascular Notch pathway genes disregulated by DLL4 reduction are themselves, like all other vascular genes, likely to be direct ETS factor targets, suggesting that the hypersprouting routinely seen after Dll4 disruption may also be indirectly repressed by the general suppression of MEF2-ETS-Notch pathway gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…The challenge in understanding the phenotypes after Mef2 ablation comes because individual loss of different genes required during sprouting angiogenesis can result in vastly different consequences. While depletion of Dll4 levels can have a proangiogenic effect, loss or depletion of direct MEF2 targets ETS1, ELK3, and HLX can have anti-angiogenic effects in vivo (Pham et al 2007;Wei et al 2009;Herbert et al 2012;Weinl et al 2014). Furthermore, the vascular Notch pathway genes disregulated by DLL4 reduction are themselves, like all other vascular genes, likely to be direct ETS factor targets, suggesting that the hypersprouting routinely seen after Dll4 disruption may also be indirectly repressed by the general suppression of MEF2-ETS-Notch pathway gene activation.…”
Section: Discussionmentioning
confidence: 99%
“…Scar-associated endothelial cells displayed enhanced expression of the ELK3 regulon ( Fig. 4g), a transcription factor known to modulate angiogenesis 46 . Metagene signature analysis found that Endo(6) (SAEndo(1)) cells expressed fibrogenic genes including PDGFD, PDGFB, LOX, LOXL2 and several basement membrane components [47][48][49] ; associated significant ontology terms included extracellular matrix organization and wound healing (signature A; Extended Data Fig.…”
Section: Distinct Endothelial Subpopulations Inhabit the Fibrotic Nichementioning
confidence: 99%
“…Genetically, the TCFs are at least partly functionally redundant (Costello et al., 2010, Weinl et al., 2014) and may also function independently of SRF (Boros et al., 2009a, Boros et al., 2009b, Buchwalter et al., 2005). Although they have been implicated in proliferation and cancer (Vickers et al., 2004, Wozniak et al., 2012, Yang et al., 2012), the extent to which the immediate-early transcriptional response is TCF-dependent, and the target genes involved, has not been systematically investigated.…”
Section: Introductionmentioning
confidence: 99%